Matematika pada kompetensi teknik dan bisnis sepeda motor - Ai Tusi fatimah; Nur Eva Zakiah (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2019)
This study aims to describe the mathematical needs that support competency in the Technical and Business of Motorcycle. This study involved the participation of teachers of Technical and Motorcycle Business and automotive engineering academics. Participants were vocational teachers and lecturers in the Ciamis and Tasikmalaya areas who were accessed by researchers. Data on mathematical needs in technical and motorcycle business are obtained from views of participants and vocational document searches. Participants identify the mathematical needs of the basic competencies in subjects of expertise competency (C3). The results of the study were obtained: (1) measurement, numbers, geometry, algebra, and statistics is the scope of mathematics that supports the competency in the Technical and Business of Motorcycle with an emphasis on the concept of comparison, area, volume, function, and conversion; (2) mathematical relational understanding is needed to solve problems. These results indicate that mathematics with mathematical understanding is needed in the Technical and Motorcycle Business Competencies.